A NEW OIL SEEPAGE IN THE OMAN MOUNTAINS AND ITS GEOLOGICAL, GEOCHEMICAL AND PETROLEUM SYSTEMS CONTEXT. (21st December 2021) - Al Kindi, Mohammed; Al‐Ghammari, Mohammed; Heward, Alan; Taylor, Paul; Siavalas, George
Abstract : A minor natural oil seepage is described from an unlikely setting in the Oman Mountains. The host rocks are fractured pelagic limestones of the lower member of the Triassic – Lower Jurassic Matbat Formation of the Hamrat Duru Group in the lower part of the allochthonous Hawasina Complex. This paper summarises Oman's established oil families and documents previously recorded oil seepages as context for describing the new seepage, its geochemistry, and possible source rock. The seep oil is different to those known from Oman's oil fields and probably derived from a poor quality, Mesozoic clastic source rock containing a mix of terrigenous and marine organic matter. The most likely source appears to be the Toarcian turbiditic upper member of the Matbat Formation, equivalent to the clastic Mafraq Formation of the Arabian Platform. The occurrence of source rocks in the allochthonous sediments of the NeoTethyan Hawasina Basin has been suspected previously, though their commercial significance remains to be established.